2016
DOI: 10.1177/2325967115627608
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Scapular Dyskinesis in Overhead and Nonoverhead Athletes

Abstract: Background:Scapular dyskinesis, or abnormal dynamic scapular control, is a condition that is commonly associated with shoulder pathology but is also present in asymptomatic individuals. Literature varies on whether it represents a cause or symptom of shoulder pathology, but it is believed to be a risk factor for further injury. Clinical identification focuses on visual observation and examination maneuvers. Treatment of altered scapular motion has been shown to improve shoulder symptoms. It is thought to be mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 32 publications
(149 reference statements)
0
66
0
7
Order By: Relevance
“…To answer this question, the prevalence of scapular dyskinesis in asymptomatic athletes and the risk of shoulder pain in athletes without scapular dyskinesis must be taken into account 33. Recent evidence suggests a 54% prevalence of scapular dyskinesis in asymptomatic overhead athletes 23. According to the results of the current review, the 46% of athletes without scapular dyskinesis would be exposed to a 25% risk, leading to 11 athletes in 100 developing shoulder pain.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…To answer this question, the prevalence of scapular dyskinesis in asymptomatic athletes and the risk of shoulder pain in athletes without scapular dyskinesis must be taken into account 33. Recent evidence suggests a 54% prevalence of scapular dyskinesis in asymptomatic overhead athletes 23. According to the results of the current review, the 46% of athletes without scapular dyskinesis would be exposed to a 25% risk, leading to 11 athletes in 100 developing shoulder pain.…”
Section: Discussionmentioning
confidence: 92%
“…The cross-sectional nature of the studies in previous reviews means one cannot determine whether scapular dyskinesis contributed to the development of shoulder pain or whether it arose subsequent to shoulder pain. Scapular dyskinesis is highly prevalent in the asymptomatic general population23 and substantially higher in overhead athletes 23. It remains unclear if dyskinesis is a sports-specific adoption that is potentially beneficial for maximal performance and protective against injury.…”
Section: Introductionmentioning
confidence: 99%
“…Visible alterations (winging or asymmetry) in the position and the motion of the scapula have been termed scapular dyskinesis [38], responsible for changes in activation of scapular stabilizing muscles [39]. Burn and colleagues [40] reported that overhead athletes have greater prevalence of developing scapular dyskinesis than non-overhead athletes, found to be present in 61% of overhead athletes. Cools and colleagues [22] highlighted the scapular dyskinesis as a possible variable for shoulder pathology in tennis players.…”
Section: Dyskinesiamentioning
confidence: 99%
“…25,26 Indeed, scapular dyskinesis is characterized by a prominent scapular medial border and an inferior angle, early scapular elevation, or inadequate scapular upward and downward rotation during arm lifting or lowering. 15,16 Previous studies have claimed that 33%-100% of the patients with various shoulder disorders, like subacromial impingement syndrome (SIS), show scapular dyskinesis 4,33 ; however, it is frequently observed in asymptomatic individuals. 33 Preziosi Standoli et al, 34 in their recent study, reported scapular dyskinesis in 8.5% of asymptomatic elite young swimmers.…”
mentioning
confidence: 99%